ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TEBU DENGAN METODE STOCKHASTIC PADA PTPN IX (PERSERO) PG MOJO SRAGEN - Haritsah, Septi Nur; Sunarso, Y. Djoko Suseno & (Universitas Slamet Riyadi, 2018)
The purpose of this study was to analyze the efficiency of the supply of raw material needs carried out by PG Mojo Sragen, so that the company can maintain the stability of the production process and to analyze the efficiency of the cost of raw material inventory with production costs incurred by PG Mojo Sragen. This type of research is a case study at PG Mojo Sragen. This type of data uses qualitative and quantitative data. Data sources use primary and secondary data sources. The data analysis technique used in this study is a stockhastic inventory control model using 90% and 95% service levels. The results showed that the control of raw material inventory implemented by PG Mojo Sragen had not yet reached the level of efficiency of raw material inventory and cost efficiency. This is indicated by the results of calculations that have been carried out by the stockhastic method can produce efficiency of raw material inventory costs rather than the methods applied by the company.Keywords: stockhastic inventory model, raw material inventory, safety stock, efficiency.